Reactive Oxygen Species Donors Increase the Responsiveness of Dorsal Horn Neurons and Induce Mechanical Hyperalgesia in Rats - Hee Young Kim; Inhyung Lee; Sang Woo Chun; Hee Kee Kim (Neural Plasticity)
Our previous studies suggest that reactive oxygen species (ROS) scavengers have analgesic effect on neuropathic pain through spinal mechanisms in the rat. The studies suggest that superoxide in spinal cord is one of important mediators of persistent pain. To test the hypothesis that increase of superoxide-derived intermediates leads to central sensitization and pain, the effects of an intrathecal injection of chemical ROS donors releasing either OH∙, OCl-, or H2O2 were examined on pain behaviors. Following treatment with t-BOOH (OH∙ donor), dorsal horn neuron responses to mechanical stimuli in normal rats and the changes of neuronal excitability were explored on substantia gelatinosa (SG) neurons using whole-cell patch clamping recordings. Intrathecal administration of t-BOOH or NaOCl (OCl- donor), but not H2O2, significantly decreased mechanical thresholds of hind paws. The responses of wide dynamic range neurons to mechanical stimuli increased after a local application of t-BOOH. The t-BOOH increased the frequency and the amplitude of excitatory postsynaptic potentials, depolarized membrane potential in SG neurons, and increased the frequency of action potentials evoked by depolarizing current pulses. These results suggest that elevated ROS, especially OH∙, in the spinal cord sensitized dorsal horn neurons and produced hyperalgesia in normal rats.